Battery, preparation method thereof and power utilization device

By controlling the mass proportion of water in the battery pole and the content of the first lithium salt in the electrolyte, the problem of short cycle life of the secondary battery is solved, and a significant improvement in battery life is achieved.

CN119833763APending Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510024693.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-03
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The cycle life of existing secondary batteries is relatively short, mainly due to the high water content in the electrolyte, causing damage to the positive and negative electrodes.

Method used

By controlling the mass proportion of water in the positive electrode sheet and the negative electrode sheet, and adding the first lithium salt to the electrolyte, its content is controlled between 3%-10%, to reduce the water content and HF production in the electrolyte.

Benefits of technology

It significantly reduces the damage to the positive and negative electrodes of the battery by the generation of HF in the electrolyte and improves the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833763A_ABST
    Figure CN119833763A_ABST
Patent Text Reader

Abstract

The invention discloses a battery, a preparation method thereof and a power utilization device, the battery comprises a positive pole piece, a negative pole piece and an electrolyte, based on the total mass of the positive pole piece, the mass ratio of water is 50 ppm to 300 ppm, and based on the total mass of the negative pole piece, the mass ratio of water is 30 ppm to 200 ppm; the electrolyte comprises a first lithium salt, the first lithium salt comprises LiN (SO2R) 2, R comprises at least one of F or F-substituted hydrocarbyl with 1-3 carbon atoms, and based on the total mass of the electrolyte, the mass ratio of the first lithium salt is 3%-10%. The battery provided by the invention is excellent in cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Priority information

[0002] This application claims priority and benefits of patent application 202410407325.5 filed with the State Intellectual Property Office of China on April 3, 2024, and the entire text of which is incorporated herein by reference. Technical Field

[0003] The present application belongs to the field of batteries, and specifically relates to a battery and an electrical device. Background Art

[0004] Secondary batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As the application range of batteries becomes wider and wider, the requirements for the performance of secondary batteries are becoming increasingly stringent, and the existing secondary batteries have a short cycle life. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides a battery, aiming to improve the cycle life of the secondary battery.

[0006] In order to achieve the above-mentioned object, the first aspect of the present application proposes a battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the mass proportion of water is 50ppm-300ppm based on the total mass of the positive electrode sheet, and the mass proportion of water is 30ppm-200ppm based on the total mass of the negative electrode sheet; the electrolyte comprises a first lithium salt, and the first lithium salt comprises:

[0007] LiN(SO2R)2,

[0008] Wherein, R includes at least one of F or a hydrocarbon group of 1 to 3 carbon atoms substituted by F, and based on the total mass of the electrolyte, the mass proportion of the first lithium salt is 3% to 10%.

[0009] The present application includes at least the following beneficial effects: in the battery of the present application, controlling the mass proportion of water in the positive electrode plate and the negative electrode plate, adding a first lithium salt to the electrolyte and controlling its content can significantly reduce the water content in the electrolyte, thereby reducing the damage caused by the generation of HF in the electrolyte to the positive and negative electrodes of the battery, and improving the cycle life of the battery.

[0010] In some embodiments, based on the total mass of the positive electrode sheet, the mass proportion of water is 100ppm-300ppm, thereby greatly improving the cycle life of the battery.

[0011] In some embodiments, based on the total mass of the positive electrode sheet, the mass proportion of water is 100ppm-250ppm, thereby greatly improving the cycle life of the battery.

[0012] In some embodiments, based on the total mass of the negative electrode plate, the mass proportion of water is 50ppm-200ppm, thereby greatly improving the cycle life of the battery.

[0013] In some embodiments, based on the total mass of the negative electrode plate, the mass proportion of water is 50ppm-150ppm, thereby greatly improving the cycle life of the battery.

[0014] In some embodiments, based on the total mass of the positive electrode sheet, the mass proportion of water is 50ppm-250ppm, thereby greatly improving the cycle life of the battery.

[0015] In some embodiments, based on the total mass of the positive electrode sheet, the mass proportion of water is 50ppm-220ppm, thereby greatly improving the cycle life of the battery.

[0016] In some embodiments, based on the total mass of the negative electrode plate, the mass proportion of water is 30ppm-150ppm, thereby greatly improving the cycle life of the battery.

[0017] In some embodiments, based on the total mass of the negative electrode plate, the mass proportion of water is 30ppm-110ppm, thereby greatly improving the cycle life of the battery.

[0018] In some embodiments, the first lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide, thereby improving the cycle life of the battery.

[0019] In some embodiments, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes LiMn x Fe 1-x-y M y PO4, wherein 0≤x≤1, 0≤y≤0.04, and M includes at least one of Ti, Mg, Ta, Sc, Cr, Y, Zr, Nb, Mo, La, Ta, W, Hf, V, Ni, Rh, or Os. Thus, the cycle life of the battery can be improved.

[0020] In some embodiments, the BET specific surface area of ​​the positive electrode active material is 10 m 2 / g-15m 2 / g. Thus, the cycle life of the battery can be improved.

[0021] In some embodiments, the positive electrode active material further comprises a LiMn x Fe 1-x-y M y A coating material covering at least part of the surface of PO4, wherein the coating material comprises carbon.

[0022] In some embodiments, based on the total mass of the positive electrode active material, the mass proportion of the coating material is 0.8%-3.5%, thereby improving the cycle life of the battery.

[0023] In some embodiments, based on the total mass of the positive electrode active material, the mass proportion of the coating material is 1.3%-2.5%, thereby improving the cycle life of the battery.

[0024] In some embodiments, the negative electrode plate includes a negative electrode active material, and the negative electrode active material includes a silicon-based material, thereby improving the cycle life of the battery.

[0025] In some embodiments, the volume average particle size Dv50 of the silicon-based material is less than or equal to 6 μm, thereby improving the cycle life of the battery.

[0026] In some embodiments, the volume average particle size Dv50 of the silicon-based material is 3 μm-6 μm, thereby increasing the cycle life of the battery.

[0027] In some embodiments, based on the total mass of the electrolyte and the total mass of the negative electrode active material, the mass proportion of the silicon-based material is 1%-5%, thereby improving the cycle life of the battery.

[0028] In some embodiments, the negative electrode active material further includes a second negative electrode active material, and the second negative electrode active material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material or lithium titanate. Thus, the cycle life of the battery can be improved.

[0029] In some embodiments, the volume average particle size Dv50 of the second negative electrode active material is 15 μm-20 μm, thereby improving the cycle life of the battery.

[0030] In some embodiments, the porosity of the negative electrode plate is 15%-25%, thereby increasing the cycle life of the battery.

[0031] In some embodiments, the electrolyte further includes a second lithium salt, and the second lithium salt includes at least one of LiPF6, lithium difluorooxalatoborate, lithium dioxalatoborate, or LiClO4. Thus, the cycle life of the battery can be improved.

[0032] In some embodiments, the electrolyte further comprises an additive, wherein the additive comprises at least one of LiPO2F2 or LiSO3F. Thus, the cycle life of the battery can be improved.

[0033] In some embodiments, one or more of the following conditions are met:

[0034] Based on the total mass of the electrolyte, the mass proportion of the LiPO2F2 is 0.1%-0.5%;

[0035] Based on the total mass of the electrolyte, the mass proportion of the LiSO3F is 0.1%-0.5%, thereby improving the cycle life of the battery.

[0036] In some embodiments, one or more of the following conditions are met:

[0037] Wherein, based on the total mass of the electrolyte, the mass proportion of the LiPO2F2 is less than or equal to 0.2%;

[0038] Based on the total mass of the electrolyte, the mass proportion of the LiSO3F is less than or equal to 0.1%, thereby improving the cycle life of the battery.

[0039] Based on the total mass of the electrolyte, the mass proportion of the first lithium salt is 5%-10%.

[0040] In a second aspect of the present application, the present application proposes a method for preparing the battery according to the first aspect, comprising:

[0041] Assembling the positive electrode sheet and the negative electrode sheet into a bare cell, injecting electrolyte, and obtaining a battery;

[0042] Wherein, based on the total mass of the positive electrode plate, the mass proportion of water is 50ppm-300ppm, and based on the total mass of the negative electrode plate, the mass proportion of water is 30ppm-200ppm; the electrolyte includes a first lithium salt, and the first lithium salt includes:

[0043] LiN(SO2R)2,

[0044] Wherein, R includes at least one of F or a hydrocarbon group of 1 to 3 carbon atoms substituted by F, and based on the total mass of the electrolyte, the mass proportion of the first lithium salt is 3% to 10%.

[0045] Therefore, the battery prepared in the present application controls the mass proportion of water in the positive electrode plate and the negative electrode plate, adds the first lithium salt to the electrolyte and controls its content, which can significantly reduce the water content in the electrolyte and improve the cycle life of the battery.

[0046] In some embodiments, before injecting the electrolyte, the process further includes: drying the bare battery cell, thereby increasing the cycle life of the battery.

[0047] In some embodiments, the drying temperature is 100° C.-120° C. Thus, the cycle life of the battery can be improved.

[0048] In some embodiments, the drying time is 10 hours to 20 hours, thereby increasing the cycle life of the battery.

[0049] In some embodiments, after injecting the electrolyte, the process further includes: forming a battery, thereby increasing the cycle life of the battery.

[0050] In the third aspect of the present application, the present application proposes an electrical device, including the battery described in the first aspect of the present application or the battery prepared by the method described in the second aspect.

[0051] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0053] Figure 1 is a schematic diagram of a battery according to one embodiment of the present application.

[0054] Figure 2 yes Figure 1 An exploded view of a battery according to an embodiment of the present application is shown.

[0055] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0056] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0057] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0058] Figure 6 Schematic diagram of an electrical device using a battery as a power source according to an embodiment of the present application.

[0059] Description of reference numerals:

[0060] 1 battery cell; 11 shell; 12 electrode assembly; 13 cover plate; 2 battery module; 3 battery pack; 31 upper box body; 32 lower box body. DETAILED DESCRIPTION

[0061] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0062] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0063] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. For example, if a range of 60-120 and 80-110 is listed for a particular parameter, it is understood that the range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" represents that all real numbers between "0-5" have been fully listed herein, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0064] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0065] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0066] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0067] At present, from the perspective of market development, the application of secondary batteries is becoming more and more extensive. Secondary batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields.

[0068] In secondary batteries, the electrolyte is generally a non-aqueous electrolyte. The presence of trace amounts of water in the electrolyte is beneficial to the formation of the SEI film of lithium-ion batteries and the improvement of battery performance. However, when the electrolyte contains excessive water, the excess water may react with the lithium salt (such as LiPF6) in the electrolyte to generate HF or even phosphoric acid, resulting in the loss of lithium salts. The generated acid will also corrode the positive and negative electrodes, causing the battery life to decay. In addition, after the battery is prepared, water in the positive electrode, negative electrode, isolation membrane, etc. may also enter the electrolyte, causing the water content in the electrolyte to increase, resulting in a decrease in the battery cycle life.

[0069] In the present application, the first lithium salt in the electrolyte is relatively stable and does not react easily with water, which can reduce the generation of HF or even acids such as phosphoric acid in the electrolyte, reduce the loss of the first lithium salt, and reduce the corrosion of the generated acid to the positive electrode plate and the negative electrode plate, thereby improving the life of the battery; however, the first lithium salt has a strong polarity and is easy to absorb water, making it easier for the water in the positive electrode plate and the negative electrode plate to enter the electrolyte, resulting in excessive water in the electrolyte, which will cause the battery life to decay. Therefore, the content of the first lithium salt in the electrolyte is controlled within the range of 3%-10%, and the water content in the positive electrode plate is correspondingly controlled within the range of 50ppm-300ppm, and the water content in the negative electrode plate is correspondingly controlled within the range of 30ppm-200ppm. On the one hand, the first lithium salt can absorb part of the water in the positive electrode plate and the negative electrode plate into the electrolyte, and this part of water is helpful for the formation of the battery SEI film and the improvement of the battery cycle performance; on the other hand, it prevents too much water from entering the electrolyte from the positive electrode plate and the negative electrode plate, and due to the stability of the first lithium salt itself, the stability of the electrolyte can be improved, which can further improve the cycle life of the battery.

[0070] The battery disclosed in the embodiment of the present application includes a lithium-ion battery, and the battery disclosed in the embodiment of the present application can be used in electrical equipment using the battery as a power source or various energy storage systems using the battery as an energy storage element. Electrical equipment may include, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.

[0071] In a first aspect, the present application provides a battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, the mass proportion of water based on the total mass of the positive electrode sheet is 50ppm-300ppm, and the mass proportion of water based on the total mass of the negative electrode sheet is 30ppm-200ppm; the electrolyte comprises a first lithium salt, and the first lithium salt comprises:

[0072] LiN(SO2R)2,

[0073] Wherein, R includes at least one of F or a hydrocarbon group of 1 to 3 carbon atoms substituted by F, and based on the total mass of the electrolyte, the mass proportion of the first lithium salt is 3% to 10%.

[0074] As an example, when R includes a hydrocarbon group of 1-3 carbon atoms substituted with F, the number of carbon atoms in the hydrocarbon group can be 1-3, 1-2, 2-3, etc.

[0075] In the battery of the present application, the first lithium salt in the electrolyte is relatively stable and does not react easily with water, which can reduce the generation of HF or even acids such as phosphoric acid in the electrolyte, reduce the loss of the first lithium salt, and can reduce the corrosion of the generated acid to the positive electrode plate and the negative electrode plate, thereby improving the life of the battery; however, the first lithium salt has a strong polarity and is easy to absorb water, making it easier for the water in the positive electrode plate and the negative electrode plate to enter the electrolyte, resulting in excessive water in the electrolyte, which will cause the battery life to decay. Therefore, the content of the first lithium salt in the electrolyte is controlled within the range of 3%-10%, and the water content in the positive electrode sheet is correspondingly controlled within the range of 50ppm-300ppm, and the water content in the negative electrode sheet is correspondingly controlled within the range of 30ppm-200ppm. On the one hand, the first lithium salt can absorb a portion of the water in the positive electrode sheet and the negative electrode sheet into the electrolyte in an appropriate amount, and this portion of water is helpful for the formation of the battery SEI film and the improvement of the battery cycle performance; on the other hand, it prevents too much water from entering the electrolyte in the positive electrode sheet and the negative electrode sheet, and due to the stability of the first lithium salt itself, the stability of the electrolyte can be improved, and the cycle life of the battery can be further improved. In summary, the battery proposed in this application has an excellent cycle life.

[0076] In some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the first lithium salt is 3%-10%. For example, based on the total mass of the electrolyte, the mass proportion of the first lithium salt can be 3%-9.9%, 5.5%-9.5%, 6%-9%, 6.5%-8.5%, 7%-8%, etc. The mass proportion of the first lithium salt in the electrolyte is controlled within the above range. On the one hand, the first lithium salt can absorb a portion of the water in the positive electrode sheet and the negative electrode sheet into the electrolyte in an appropriate amount, and this portion of water has an effect on the formation and On the other hand, the first lithium salt has a strong polarity. Controlling the content of the first lithium salt within the above range can reduce the excessive absorption of water in the positive electrode sheet and the negative electrode sheet into the electrolyte due to excessive first lithium salt, so that the water entering the electrolyte from the positive electrode sheet and the negative electrode sheet will not be too much. It can also reduce the lack of water in the electrolyte caused by too little first lithium salt, which is not conducive to the formation of the battery SEI film and the improvement of the battery cycle performance. In addition, due to the stability of the first lithium salt itself, the stability of the electrolyte can be improved, and the cycle life of the battery can be further improved.

[0077] In some other embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the first lithium salt is 5%-10%. It can be understood that the first lithium salt will be consumed during the battery formation process (for example, participating in the formation of SEI). Therefore, 5%-10% can be understood as the content of the first lithium salt in the battery electrolyte before formation. After formation, its content may be slightly reduced. For example, before formation, the mass proportion of the first lithium salt in the electrolyte is 5%, and after formation, the mass proportion of the first lithium salt in the electrolyte becomes 3%. Regardless of whether the battery has been formed or not, as long as the content of the first lithium salt in its electrolyte (3%-10%) meets the limitations of the claims of this application, it falls within the scope of protection of this application.

[0078] It can be understood that “the mass proportion of the first lithium salt based on the total mass of the electrolyte” is a well-known definition in the art and can be measured by methods well-known in the art, for example, the following method can be used for measurement:

[0079] The battery was disassembled, and the electrolyte was taken out. Referring to the standard JY / T020-1996 "General Rules for Ion Chromatography Analysis Methods", an ion chromatograph (model Thermo Nicolet IS10) was used to measure the mass proportion of the first lithium salt in the electrolyte.

[0080] In some embodiments of the present application, based on the total mass of the positive electrode sheet, the mass proportion of water is 50ppm-300ppm. For example, based on the total mass of the electrolyte, based on the total mass of the positive electrode sheet, the mass proportion of water can be 50ppm-299ppm, 110ppm-290ppm, 120ppm-280ppm, 130ppm-270ppm, 140ppm-260ppm, 150ppm-250ppm, 160ppm-240ppm, 170ppm-230ppm, 180ppm-220ppm, 190ppm-210ppm, etc. The water content in the positive electrode sheet is controlled within the above range, and the first lithium salt can absorb a portion of the water in the positive electrode sheet into the electrolyte in an appropriate amount, which is helpful for the formation of the battery SEI film and the improvement of the battery cycle performance; and the water in the positive electrode sheet that does not enter the electrolyte is too much, which can improve the stability of the electrolyte and further improve the cycle life of the battery.

[0081] In other embodiments of the present application, based on the total mass of the positive electrode plate, the mass proportion of water is 100ppm-300ppm, for example, based on the total mass of the positive electrode plate, the mass proportion of water is 100ppm-250ppm. At this time, the secondary battery can be a battery that has not been formed, that is, before formation, and the water content of its positive electrode plate is slightly higher than the water content of the positive electrode plate of the formed battery. For example, before formation, the mass proportion of water in the positive electrode plate is 100ppm-300ppm, and the mass proportion of water in the positive electrode plate after formation is 50ppm-250ppm, which can improve the stability of the electrolyte and further improve the cycle life of the battery.

[0082] It can be understood that the preparation process of the battery includes assembling the positive electrode plate, the negative electrode plate, the isolation membrane, etc. into a bare battery cell, drying, and then injecting the electrolyte. It also goes through packaging, standing, formation, shaping and other processes to form a battery cell. When the water content of the electrode (positive electrode plate, negative electrode plate) is limited to the water content before formation, it refers to the water content of the electrode after drying and before injecting the electrolyte.

[0083] In other embodiments of the present application, based on the total mass of the positive electrode plate, the mass proportion of water is 50ppm-250ppm. For example, based on the total mass of the positive electrode plate, the mass proportion of water is 50ppm-220ppm. At this time, the secondary battery can be a battery after formation. Since a part of the water in the plate enters the electrolyte after formation, the water content of the positive electrode plate is slightly lower than that of the positive electrode plate of the battery that has not been formed, which can improve the stability of the electrolyte and further improve the cycle life of the battery.

[0084] It can be understood that when the water content of the positive electrode plate and the negative electrode plate is determined, if there is too much first lithium salt, more water will enter the electrolyte, and too much water will be detrimental to the cycle performance of the battery; if there is too little first lithium salt, less water will enter the electrolyte, and too little water will also affect the formation of the battery SEI film and the improvement of battery performance; similarly, when the content of the first lithium salt in the electrolyte is determined, if there is too much water in the positive electrode plate and the negative electrode plate, more water will enter the electrolyte, and if there is too little water in the positive electrode plate and the negative electrode plate, less water will enter the electrolyte; therefore, the embodiment of the present application controls the water content of the positive electrode plate (50ppm-300ppm), the water content of the negative electrode plate (30ppm-200ppm) and the content of the first lithium salt (3%-10% by mass in the electrolyte) at the same time, so that the amount of water entering the electrolyte is optimal, not too much, not too little, so as to achieve the optimal battery cycle life.

[0085] It can be understood that "the mass proportion of water based on the total mass of the positive electrode sheet" can be interpreted as the number of micrograms of water contained in each gram of the positive electrode sheet on average. For example, based on the total mass of the positive electrode sheet, the mass proportion of water is 100 ppm, indicating that on average 1 gram of the positive electrode sheet contains 100 μg of water. "Based on the total mass of the positive electrode sheet, the mass proportion of water" can be measured by methods known in the art, for example, it can be measured by the following method:

[0086] Referring to the standard GB / T 6283-2008, the battery is disassembled to obtain the positive electrode sheet, the positive electrode sheet is crushed, and the Karl Fischer method (direct coulometric titration) is used for determination. This is a very sensitive chemical analysis method suitable for the determination of trace moisture. In short, the method includes:

[0087] Electrode water content test method:

[0088] 1. When the battery is fully discharged, perform the following operations in an environment with a humidity of less than 2:

[0089] 2. Disassemble the battery, take out the positive electrode, and soak it in DMC (dimethyl carbonate) for more than 2 hours;

[0090] 3. Pour out the DMC and let the electrode dry naturally;

[0091] 4. Take a number of electrodes, record the electrode mass m1, and test it using the following instrument: Fully automatic water content tester (model: Swiss Metrohm 874+831). Enter m1 in the instrument, and the instrument automatically outputs the electrode water content.

[0092] It can be understood that in the examples of the present application, 1ppm=1μg / g.

[0093] In some embodiments of the present application, based on the total mass of the negative electrode plate, the mass proportion of water is 30ppm-200ppm. For example, based on the total mass of the negative electrode plate, the mass proportion of water can be 30ppm-199ppm, 60ppm-190ppm, 70ppm-180ppm, 80ppm-170ppm, 90ppm-160ppm, 100ppm-150ppm, 110ppm-140ppm, 120ppm-130ppm, etc. Specifically, the water content in the negative electrode plate is controlled within the above range, and the first lithium salt can absorb a portion of the water in the negative electrode plate into the electrolyte in an appropriate amount, which is helpful for the formation of the battery SEI film and the improvement of the battery cycle performance; and the water in the negative electrode plate does not enter the electrolyte too much, which can improve the stability of the electrolyte and further improve the cycle life of the battery.

[0094] In other embodiments of the present application, based on the total mass of the negative electrode plate, the mass proportion of water is 50ppm-200ppm. For example, based on the total mass of the negative electrode plate, the mass proportion of water is 50ppm-150ppm. At this time, the secondary battery can be a battery that has not been formed, that is, before formation, and the water content of its negative electrode plate is slightly higher than that of the negative electrode plate of the battery that has been formed. For example, before formation, the mass proportion of water in the negative electrode plate is 50ppm-200ppm, and after formation, the mass proportion of water in the negative electrode plate is 30ppm-150ppm, which can improve the stability of the electrolyte and further improve the cycle life of the battery.

[0095] In other embodiments of the present application, based on the total mass of the negative electrode plate, the mass proportion of water is 30ppm-150ppm. For example, based on the total mass of the negative electrode plate, the mass proportion of water is 30ppm-110ppm. At this time, the secondary battery can be a battery after formation, and the water content of its negative electrode plate is slightly lower than that of the negative electrode plate of a battery that has not been formed, which can improve the stability of the electrolyte and further improve the cycle life of the battery.

[0096] It can be understood that “the mass proportion of water based on the total mass of the negative electrode plate” is a well-known definition in the art and can be measured by methods well-known in the art, for example, the following method can be used for measurement:

[0097] Referring to the standard GB / T 6283-2008, the battery is disassembled to obtain the negative electrode sheet, the negative electrode sheet is crushed, and the Karl Fischer method (direct coulometric titration method) is used for determination. This method is basically the same as the previous method for detecting the water content of the positive electrode sheet, and will not be repeated here.

[0098] Based on the total mass of the negative electrode plate and the mass proportion of water, the detailed testing method is the same as that of the positive electrode plate and will not be repeated here.

[0099] It can be understood that after the battery is formed, part of the water in the positive electrode sheet and the negative electrode sheet enters the electrolyte and is consumed. Therefore, after the battery is formed, the water content in the positive electrode sheet and the negative electrode sheet decreases compared to before the formation. Regardless of whether the battery has been formed or not, and regardless of whether the battery has not been cycled after formation, or after any number of cycles, as long as the water content of the positive electrode sheet (50ppm-300ppm), the water content of the negative electrode sheet (30ppm-200ppm), and the content of the first lithium salt in the electrolyte (3%-10%) meet the limitations of the claims of this application, they all fall within the scope of protection of this application. The limitations of other contents below are similar and will not be repeated here.

[0100] In some embodiments of the present application, the first lithium salt includes at least one of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (CAS No. 90076-65-6). Specifically, the first lithium salt in the electrolyte is relatively stable and does not react easily with water. It can absorb a portion of the water in the positive electrode plate into the electrolyte in an appropriate amount. This portion of water is helpful for the formation of the battery SEI film and the improvement of the battery cycle performance; and it prevents too much water from entering the electrolyte in the positive electrode plate. Due to the stability of the first lithium salt itself, the stability of the electrolyte can be improved, and the cycle life of the battery can be further improved.

[0101] In some embodiments of the present application, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes LiMn x Fe 1-x-y M yPO4, wherein 0≤x≤1, 0≤y≤0.04, M includes at least one of Ti, Mg, Ta, Sc, Cr, Y, Zr, Nb, Mo, La, Ta, W, Hf, V, Ni, Rh or Os, for example, 0≤x≤0.99, 0.1≤x≤0.9, 0.2≤x≤0.8, 0.3≤x≤0.7, 0.4≤x≤0.5, etc., 0≤y≤0.03, 0.01≤y≤0.02, etc. Specifically, the above-mentioned positive electrode active material is a lithium iron phosphate positive electrode active material, and the lithium iron phosphate positive electrode active material is a lithium iron phosphate positive electrode active material. The moisture in the active material includes bound water and adsorbed water. Due to its own structure, the bound water is difficult to dry. The water content in the positive electrode plate is controlled in the range of 50ppm-300ppm. The moisture in the lithium iron phosphate positive active material is basically bound water. The first lithium salt can absorb a part of the above-mentioned bound water in the positive electrode plate into the electrolyte in an appropriate amount, thereby improving the cycle life of the battery. In addition, the electrochemical properties of the lithium iron phosphate positive active material itself are relatively stable, with a stable charge and discharge platform, which can further improve the cycle life of the battery.

[0102] On the other hand, LiMn x Fe 1-x-y M y The water content in the positive and negative electrodes of PO4 is controlled within the above range. When multiple batteries are assembled into a battery module or a battery pack, the difference in water content among the batteries in the battery module or battery pack can be made smaller, that is, the water content in each battery has good consistency, thereby reducing the poor long-term cycle life of the battery module or battery pack caused by poor consistency and improving the cycle life of the entire battery module or battery pack.

[0103] In some embodiments of the present application, the positive electrode active material further comprises a LiMn x Fe 1-x-y M y The coating material on at least part of the surface of PO4 includes carbon. The presence of the coating material carbon may affect the water content of the positive electrode plate, and the coating material is arranged on the surface of the lithium iron phosphate positive electrode active material to improve the electronic conductivity of the positive electrode active material and improve the cycle life of the battery.

[0104] In some embodiments of the present application, based on the total mass of the positive electrode active material, the mass proportion of the coating material is 0.8%-3.5%. For example, it can be 0.8%-3.4%, 1%-3%, 1.5%-2.5%, etc. Controlling the mass proportion of the coating material within the above range may be beneficial to control the water content of the positive electrode sheet within the required range, and can reduce the insufficient conductivity of the positive electrode active material caused by too low a coating material content, and reduce the coating material being too thick and the ion transmission path being too long caused by too high a coating material content, further improving the cycle life of the battery. In other embodiments of the present application, based on the total mass of the positive electrode active material, the mass proportion of the coating material is 1.3%-2.5%.

[0105] In some embodiments of the present application, the BET specific surface area of ​​the positive electrode active material is 10 m 2 / g-15m 2 / g. For example, the BET specific surface area of ​​the positive electrode active material can be 10m 2 / g-14.9m 2 / g,11m 2 / g-14m 2 / g,12m 2 / g-13m 2 / g, etc., thereby controlling the BET specific surface area of ​​the positive electrode active material within the above range, so that the water in the obtained positive electrode plate is easier to dry, and the problem of the positive electrode plate easily absorbing water caused by the excessively large BET specific surface area can be reduced. At the same time, the problem of the water in the negative electrode plate being difficult to dry caused by the excessively small BET specific surface area can be reduced, thereby improving the cycle life of the battery.

[0106] It is understood that the “BET specific surface area of ​​the positive electrode active material” is a well-known definition in the art and can be measured by methods well-known in the art. For example, it can be measured by the following method:

[0107] After the positive electrode active material is scraped, the specific surface area is determined by the specific surface area meter-static capacity method according to the reference standard GB / T19587-2017. Specifically, according to the embodiment of the present application, a flow method gas adsorption type specific surface area measuring device (model AUY220) can be used for measurement.

[0108] In some embodiments of the present application, the negative electrode plate includes a negative electrode active material, and the negative electrode active material includes a silicon-based material. Specifically, since the silicon-based material has many hydroxyl groups on the surface, it is sensitive to water or HF generated by water and is easily corroded by water or HF. The battery within the water content range of the positive electrode plate and the negative electrode plate of the present application has little damage to the silicon-based material, and the theoretical capacity of the silicon-based material is high, so that the battery has excellent energy density and cycle performance.

[0109] It is understandable that silicon-based materials refer to materials containing silicon. As examples, silicon-based materials include but are not limited to at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, lithium-containing silicon-carbon materials, lithium-containing silicon oxide materials, magnesium-containing silicon-carbon materials and magnesium-containing silicon oxide materials, silicon-nitrogen composites and silicon alloys.

[0110] In some embodiments of the present application, the volume average particle size Dv50 of the silicon-based material is less than or equal to 6μm. For example, the volume average particle size Dv50 of the silicon-based material can be 0.1μm-5.9μm, 0.5μm-5.5μm, 1μm-5μm, 1.5μm-4.5μm, 2μm-4μm, 2.5μm-3.5μm, etc. In other embodiments of the present application, the volume average particle size Dv50 of the silicon-based material is 3μm-6μm. Specifically, silicon-based materials are sensitive to water or HF generated by water due to the large number of hydroxyl groups on their surfaces, and are easily corroded by water or HF. The smaller the particle size of the silicon-based material, the more serious the corrosion. The present application controls the water content in the positive electrode plate and the negative electrode plate and controls the content of the first lithium salt in the electrolyte, which can inhibit the continuous increase of water in the electrolyte and reduce the corrosion of silicon-based materials by water. Therefore, small-particle silicon-based materials can be used in the battery system of the present application. The volume average particle size Dv50 of the silicon-based material is controlled within the above range, which can shorten the diffusion path of lithium ions, reduce the impedance of the battery, increase the electrolyte wetting area, and thus improve the low-temperature performance of the battery. It can also reduce the increase in the reaction area caused by the too low particle size of the silicon-based material, reduce the probability of side reactions, and increase the cycle life of the battery.

[0111] It is understood that the "volume average particle size Dv50 of the silicon-based material" is a well-known definition in the art and can be measured by methods well-known in the art, for example, the following method can be used for measurement:

[0112] Referring to the standard GB / T 19077-2016, the volume average particle size Dv50 of the silicon-based material can be obtained by testing the silicon-based material using a laser particle size analyzer (such as Malvern Master Sizer3000).

[0113] In some embodiments of the present application, based on the total mass of the negative electrode active material, the mass proportion of the silicon-based material is 1%-5%. For example, based on the total mass of the negative electrode active material, the mass proportion of the silicon-based material can be 1%-4.9%, 1.5%-4.5%, 2%-4%, 2.5%-3.5%, 2.5%-3%, etc. Specifically, the content of the silicon-based material is controlled within the above range. On the one hand, the silicon-based material has a high capacity, and under the condition of the same energy density, the coating thickness of the negative electrode active material layer on the negative electrode plate can be reduced, thereby effectively reducing the migration distance of lithium ions between the negative electrode active material layers, so that the efficiency of lithium ion transmission is high and the cycle life of the battery is improved; on the other hand, since the first lithium salt can absorb part of the water in the positive electrode plate and the negative electrode plate into the electrolyte, controlling the amount of silicon-based material added can reduce the increase in the probability of contact with water caused by excessive addition of silicon-based material, further reduce the damage of water to the silicon-based material, and improve the cycle life of the battery.

[0114] It is understood that “the mass proportion of the silicon-based material based on the total mass of the negative electrode active material” is a well-known definition in the art and can be measured by methods well-known in the art. For example, it can be measured by the following method:

[0115] The negative electrode sheet is scraped into powder, dissolved with nitric acid, and elemental analysis is performed by inductively coupled plasma emission spectrometry (ICP, Ametek, model: SPECTROARCOSICP-OES) according to standards YS / T1006.2-2014, GB / T23367.2-2009 or YS / T1028.5-2015 to determine the composition and content of silicon element, and then obtain the mass percentage of silicon-based materials.

[0116] In some embodiments of the present application, the negative electrode active material further includes a second negative electrode active material, and the second negative electrode active material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material or lithium titanate. Therefore, the second negative electrode active material has strong stability and can further improve the cycle life of the battery.

[0117] In some embodiments, the tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0118] In some embodiments of the present application, the volume average particle size Dv50 of the second negative electrode active material is 15 μm-20 μm. For example, the volume average particle size Dv50 of the second negative electrode active material can be 15 μm-19.9 μm, 15.5 μm-19.5 μm, 16 μm-18 μm, 16.5 μm-17.5 μm, etc. Therefore, the combination of the above-mentioned second negative electrode active material with a relatively large particle size and a small particle size silicon-based material can improve the dynamic performance of the battery and increase the cycle life of the battery.

[0119] In some embodiments of the present application, the porosity of the negative electrode sheet is 15%-25%. For example, the porosity of the negative electrode sheet can be 15%-24%, 16%-23%, 17%-22%, 18%-21%, 19%-20%, etc. Specifically, controlling the porosity of the negative electrode sheet within the above range can improve the dynamic performance of the battery and the cycle life on the one hand, and on the other hand, within the above porosity range of the negative electrode sheet, the negative electrode sheet is easy to dry and reaches a water content of 50ppm-200ppm, which can improve the cycle life of the battery.

[0120] It is understood that the “porosity of the negative electrode sheet” is a well-known definition in the art and can be measured by methods well-known in the art. For example, it can be measured by the following method:

[0121] It is determined by the gas replacement method. Specifically, it can be determined by referring to GB / T24586-2009 through the following steps: The negative electrode is immersed in ethyl methyl carbonate (EMC) for cleaning. A true density analyzer (model AccuPycⅡ1340) is used to measure the porosity of the electrode, which is the percentage of the pore volume in the electrode to the total volume of the electrode. The calculation formula is: Porosity = (V-V0) / V×100%, where V0 is the true volume and V is the apparent volume.

[0122] In some embodiments of the present application, the electrolyte further includes a second lithium salt, which includes at least one of LiPF6, lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB) or LiClO4. Specifically, a small amount of the above second lithium salt can react with a trace amount of water entering the electrolyte (the first lithium salt absorbs the water in the positive electrode plate and the negative electrode plate into the electrolyte in an appropriate amount), and the generated substance can inhibit the decomposition of the first lithium salt and the second lithium salt that do not participate in the reaction in the electrolyte, play a role in stabilizing the lithium salt, and thus improve the cycle performance of the battery. In addition, the second lithium salt that participates in the reaction can consume the water that enters the electrolyte during the battery cycle, reducing the effect of excessive water on the battery cycle. Specifically, taking LiPF6 as an example, a small amount of LiPF6 can react with a trace amount of water to generate LiPO2F2, and LiPO2F2 can inhibit the decomposition of LiPF6 that does not participate in the reaction, thereby stabilizing the LiPF6 that does not participate in the reaction in the electrolyte.

[0123] In some embodiments of the present application, the electrolyte further includes an additive, and the additive includes at least one of LiPO2F2 or LiSO3F. Thus, the additive can further stabilize the electrolyte, reduce the probability of decomposition of the lithium salt (the first lithium salt and the second lithium salt or the first lithium salt), and improve the cycle life of the battery. The additive LiPO2F2 or LiSO3F can be actively added or generated by other substances.

[0124] In some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the LiPO2F2 is 0.1%-0.5%. For example, based on the total mass of the electrolyte, the mass proportion of the LiPO2F2 can be 0.1%-0.49%, 0.1%-0.4%, 0.2%-0.3%, etc. Specifically, controlling the mass proportion of LiPO2F2 in the electrolyte within the above range can further stabilize the electrolyte, reduce the probability of decomposition of the lithium salt (the first lithium salt and / or the second lithium salt), and improve the cycle life of the battery.

[0125] In other embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the LiPO2F2 is less than or equal to 0.2%. The above content may be the content of LiPO2F2 in the battery electrolyte after formation. During the formation process, LiPO2F2 may participate in the formation of the SEI film or may be passively generated. By controlling the mass proportion of LiPO2F2 in the electrolyte of the battery after formation within the above range, the electrolyte may be further stabilized, the probability of decomposition of the lithium salt (the first lithium salt and the second lithium salt or the first lithium salt) may be reduced, and the cycle life of the battery may be improved.

[0126] It is understood that "the mass proportion of LiPO2F2 based on the total mass of the electrolyte" is a well-known definition in the art and can be measured by methods well-known in the art, for example, the following method can be used for measurement:

[0127] With reference to the standard JY / T020-1996 “General Rules for Ion Chromatography Analysis Methods”, an ion chromatograph (model ThermoNicolet IS10) was used to determine the mass proportion of LiPO2F2 in the electrolyte by ion chromatography analysis method.

[0128] In some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the LiSO3F is 0.1%-0.5%. For example, based on the total mass of the electrolyte, the mass proportion of the LiSO3F can be 0.1%-0.49%, 0.1%-0.4%, 0.2%-0.3%, etc. Specifically, by controlling the mass proportion of LiSO3F in the electrolyte within the above range, the electrolyte can be further stabilized, the probability of decomposition of the lithium salt (the first lithium salt and / or the second lithium salt) can be reduced, and the cycle life of the battery can be improved.

[0129] In some other embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the LiSO3F is less than or equal to 0.1%. The above content may be the content of LiSO3F in the battery electrolyte after formation. During the formation process, LiSO3F may participate in the formation of the SEI film or may be passively generated. By controlling the mass proportion of LiSO3F in the electrolyte of the battery after formation within the above range, the electrolyte can be further stabilized, the probability of decomposition of the lithium salt (the first lithium salt and the second lithium salt or the first lithium salt) can be reduced, and the cycle life of the battery can be improved.

[0130] It is understood that “the mass proportion of LiSO3F based on the total mass of the electrolyte” is a well-known definition in the art and can be measured by methods well-known in the art, for example, the following method can be used for measurement:

[0131] With reference to the standard JY / T020-1996 “General Rules for Ion Chromatography Analysis Methods”, an ion chromatograph (model ThermoNicolet IS10) was used to determine the mass proportion of LiPO2F2 in the electrolyte by ion chromatography analysis method.

[0132] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active metal ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0133] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode active material described in the present application.

[0134] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.

[0135] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0136] In some embodiments of the present application, the positive electrode active material includes LiMn x Fe 1-x-y M y Composite material of PO4 and carbon.

[0137] In some embodiments of the present application, the positive electrode active material further includes lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811)), or lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) at least one.

[0138] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.

[0139] In the list of positive electrode active materials in this application, the molar content of oxygen is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of oxygen will fluctuate.

[0140] In some embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorine-containing acrylate resin.

[0141] In some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.

[0142] In some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0143] In some embodiments of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector.

[0144] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is disposed on any one or both of the two facing surfaces of the negative electrode current collector.

[0145] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0146] In some embodiments, the negative electrode active material layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0147] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0148] In some embodiments, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0149] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0150] In some embodiments of the present application, the electrolyte includes an electrolyte salt, a solvent and an additive.

[0151] In some embodiments of the present application, the electrolyte salt, i.e. the above-mentioned lithium salt, may also include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorobisoxalate phosphate or lithium tetrafluorooxalate phosphate.

[0152] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0153] In some embodiments of the present application, the electrolyte further includes additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0154] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.

[0155] In some embodiments of the present application, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0156] The battery of the present application includes a battery cell form, a battery module form and a battery pack form. The battery cell, battery module and battery pack of the present application are described below with reference to the accompanying drawings as appropriate.

[0157] In some embodiments of the present application, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly through a winding process or a lamination process.

[0158] In some embodiments of the present application, the battery cell may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0159] In some embodiments of the present application, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0160] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 1 is a square structure as an example.

[0161] In some embodiments of the present application, reference Figure 2 The outer packaging may include a shell 11 and a cover plate 13. Among them, the shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery cell 1 can be one or more, and those skilled in the art can select according to specific actual needs.

[0162] The second aspect of the present application provides a method for preparing the battery of the first aspect, comprising:

[0163] S100, assembling the positive electrode sheet and the negative electrode sheet into a bare cell, injecting electrolyte, and obtaining a battery;

[0164] Wherein, based on the total mass of the positive electrode plate, the mass proportion of water is 50ppm-300ppm, and based on the total mass of the negative electrode plate, the mass proportion of water is 30ppm-200ppm; the electrolyte includes a first lithium salt, and the first lithium salt includes:

[0165] LiN(SO2R)2,

[0166] Wherein, R includes at least one of F or a hydrocarbon group of 1 to 3 carbon atoms substituted by F, and based on the total mass of the electrolyte, the mass proportion of the first lithium salt is 3% to 10%.

[0167] Therefore, the battery prepared in the present application controls the mass proportion of water in the positive electrode plate, adds the first lithium salt to the electrolyte and controls its content, and the first lithium salt can absorb the above-mentioned part of the water in the positive electrode plate into the electrolyte in an appropriate amount, and this part of water is helpful for the formation of the battery SEI film and the improvement of the battery cycle performance; and it prevents too much water from entering the electrolyte from the positive electrode plate, which can improve the stability of the electrolyte and increase the cycle life of the battery.

[0168] In some embodiments of the present application, before injecting the electrolyte, the process further includes: drying the bare battery cell. Thus, by drying and controlling the water content in the positive electrode sheet and / or the negative electrode sheet, the cycle life of the battery can be increased.

[0169] In some embodiments of the present application, the water content in the positive electrode plate and / or negative electrode plate of the battery can be controlled by drying conditions such as drying method, drying temperature, drying time, etc. Drying can be performed at normal pressure, reduced pressure, microwave, infrared, etc. In other embodiments of the present application, drying is performed by normal pressure drying.

[0170] In some embodiments of the present application, the drying temperature is 100°C-120°C. For example, the drying temperature may be 100°C-119°C, 105°C-115°C, 110°C-115°C, etc. Therefore, within the above drying temperature range, it is beneficial to control the water content in the positive electrode sheet and the negative electrode sheet within a limited range, and then the first lithium salt can absorb a portion of the water in the positive electrode sheet and the negative electrode sheet into the electrolyte in an appropriate amount, and this portion of water is helpful for the formation of the battery SEI film and the improvement of the battery cycle performance; and it prevents too much water from entering the electrolyte in the negative electrode sheet, which can improve the stability of the electrolyte and further improve the cycle life of the battery.

[0171] In some embodiments of the present application, the drying time is 10h-20h. For example, the drying time can be 10h-19h, 11h-18h, 12h-17h, 13h-16h, 14h-15h, etc. Therefore, within the above drying time range, it is beneficial to control the water content in the positive electrode sheet and the negative electrode sheet within a limited range, and then the first lithium salt can absorb the above part of the water in the positive electrode sheet and the negative electrode sheet into the electrolyte in an appropriate amount, and this part of water is helpful for the formation of the battery SEI film and the improvement of the battery cycle performance; and it makes the water in the negative electrode sheet not too much to enter the electrolyte, and due to the stability of the first lithium salt itself, the stability of the electrolyte can be improved, and the cycle life of the battery can be further improved.

[0172] When the positive electrode active material is a lithium iron phosphate material, it is difficult to dry after being prepared into a positive electrode plate. Controlling the drying temperature and time within the above range is more conducive to controlling the water content in the positive electrode plate within a limited range, which can improve the stability of the electrolyte and further improve the cycle life of the battery.

[0173] Specifically, the positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, dried according to the above-mentioned drying conditions, and then the electrolyte is injected, and after vacuum packaging, standing and other processes, a lithium-ion battery is obtained.

[0174] In some embodiments of the present application, after injecting the electrolyte, the process further includes: forming a battery.

[0175] In some embodiments of the present application, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0176] Figure 3 2 is an example of a battery module 2. Figure 3In the battery module 2, the plurality of battery cells 1 may be arranged in sequence along the length direction of the battery module 2. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 1 may be fixed by fasteners.

[0177] In some embodiments of the present application, the battery module 2 may further include a housing having a receiving space, and the plurality of battery cells 1 are received in the receiving space.

[0178] In some embodiments of the present application, the battery modules mentioned above may also be assembled into a battery pack. The number of battery modules contained in the battery pack may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0179] Figure 4 and Figure 5 The battery pack 3 is used as an example. Figure 4 and Figure 5 The battery pack 3 may include a battery box and a plurality of battery modules 2 disposed in the battery box. The battery box includes an upper box body 31 and a lower box body 32. The upper box body 31 can cover the lower box body 32 and form a closed space for accommodating the battery modules 2. The plurality of battery modules 2 can be arranged in the battery box in any manner.

[0180] In addition, the present application also provides an electrical device, the electrical device comprising at least one of the battery described in the first aspect of the present application, the battery prepared by the method described in the second aspect, the battery described in the third aspect, or the battery prepared by the method described in the fourth aspect. The battery cell, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0181] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0182] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0183] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0184] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0185] Example 1

[0186] 1. Preparation of positive electrode sheet

[0187] The positive electrode active material LiFePO4 (BET specific surface area 12m 2 / g, based on the total mass of the positive electrode active material, the mass of the carbon coating material accounts for 1.2%, and the thickness of the carbon coating material is 2μm), the binder polyvinylidene fluoride, and the conductive agent acetylene black are mixed in a weight ratio of 98:1:1 and dissolved in a solvent N-methylpyrrolidone (NMP) to form a positive electrode slurry, and then the slurry is coated on the current collector aluminum foil, and after drying, it is cold pressed, trimmed, cut into pieces, and striped to form the positive electrode sheet of the lithium ion battery.

[0188] 2. Preparation of negative electrode sheet

[0189] The negative electrode active material (silicon-containing material SiO2 (volume average particle size Dv50 is 6 μm): graphite (volume average particle size Dv50 is 17.5 μm) = 5:95), conductive agent carbon black, thickener CMC, adhesive styrene butadiene rubber (SBR), and ceramic material are mixed and dissolved in solvent deionized water in a weight ratio of 95:2:1:1:1 to form a negative electrode slurry, and the negative electrode slurry is obtained under the action of a vacuum mixer; then the slurry is coated on the current collector copper foil, and after drying, cold pressing, trimming, cutting, stripping, etc. are performed to form a negative electrode sheet of a lithium-ion battery. The porosity of the negative electrode sheet is 20%.

[0190] 3. Preparation of electrolyte

[0191] The reaction was carried out in an argon atmosphere glove box with a water content of <10ppm. First, the non-aqueous solvent EC (ethylene carbonate): DMC (dimethyl carbonate): EMC (ethyl methyl carbonate) were mixed in a mass ratio of 30:50:20, and then lithium salts (LiFSI and LiPF6) were added. Finally, 2% of the additive VC (vinylene carbonate) of the total mass of the electrolyte, 0.1% of the total mass of the electrolyte LiPO2F2 and 0.1% of the total mass of the electrolyte LiSO3F were added to complete the preparation of the electrolyte. Based on the total mass of the electrolyte, the mass proportion of LiFSI was 7%, and the mass proportion of LiPF6 was 12.5%.

[0192] 4. Isolation film

[0193] A polyethylene (PE) film with a thickness of 10 μm was used as the isolation film.

[0194] 5. Preparation of secondary batteries

[0195] The positive electrode sheet, isolation film and negative electrode sheet are prepared in order, and the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. Then, the bare battery cell is wound and the tabs are welded. The bare battery cell is placed in an outer packaging shell, dried at 110°C for 13 hours, and then the electrolyte is injected. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0196] The preparation methods of the lithium-ion batteries of Examples 2-15 and Comparative Examples 1-4 are the same as those of Example 1, except that the processes for preparing the positive electrode plates are different. As shown in Table 1, in the electrolyte of Example 15, the mass ratio of LiBOB and LiPF6 in the second lithium salt is 1:1.

[0197] Table 1

[0198]

[0199]

[0200] The capacity retention rate after 1.2C cycle was tested for the batteries of Examples 1-15 and Comparative Examples 1-4. The test results are shown in Table 2.

[0201] At 25°C, charge the battery to 3.65V at 0.33C, and then discharge it to 2.0V at 0.33C. Record the discharge capacity at this time as U0. Then, charge the battery to 3.65V at 1.2C, and then discharge it to 2.0V at 0.33C. Repeat this cycle for 800 weeks and then test the discharge capacity at this time as U1.

[0202] Then the battery capacity retention rate E = (U0-U1) / U0×100%.

[0203] Table 2

[0204]

[0205]

[0206] Conclusion: Comparing Example 1-15 with Comparative Example 1-4, in Example 1-15, the mass proportion of water in the positive electrode and the negative electrode is controlled, and the first lithium salt is added to the electrolyte and its content is controlled, which can improve the cycle performance of the battery. Comparative Example 1-4 does not simultaneously control the water content of the electrode and the content of the first lithium salt, and the cycle performance of the battery is significantly reduced. It can be seen that the present application simultaneously controls the water content of the electrode and the content of the first lithium salt, which can significantly reduce the continuous increase of the water content in the electrolyte, thereby reducing the damage caused by the generation of HF in the electrolyte to the positive and negative electrodes of the battery, and improving the cycle life of the battery.

[0207] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the mass proportion of water is 50ppm-300ppm based on the total mass of the positive electrode sheet, and the mass proportion of water is 30ppm-200ppm based on the total mass of the negative electrode sheet; the electrolyte comprises a first lithium salt, and the first lithium salt comprises: LiN(SO2R)2, Wherein, R includes at least one of F or a hydrocarbon group of 1 to 3 carbon atoms substituted by F, and based on the total mass of the electrolyte, the mass proportion of the first lithium salt is 3% to 10%.

2. The battery according to claim 1, characterized in that Based on the total mass of the positive electrode plate, the mass proportion of water is 100ppm-300ppm.

3. The battery according to claim 1 or 2, characterized in that: Based on the total mass of the positive electrode plate, the mass proportion of water is 100ppm-250ppm.

4. The battery according to any one of claims 1 to 3, characterized in that Based on the total mass of the negative electrode plate, the mass proportion of water is 50ppm-200ppm.

5. The battery according to any one of claims 1 to 4, characterized in that Based on the total mass of the negative electrode plate, the mass proportion of water is 50ppm-150ppm.

6. The battery according to claim 1, characterized in that Based on the total mass of the positive electrode plate, the mass proportion of water is 50ppm-250ppm.

7. The battery according to claim 1 or 6, characterized in that: Based on the total mass of the positive electrode plate, the mass proportion of water is 50ppm-220ppm.

8. The battery according to any one of claims 1, 6 and 7, characterized in that: Based on the total mass of the negative electrode plate, the mass proportion of water is 30ppm-150ppm.

9. The battery according to any one of claims 1, 6, 7 and 8, characterized in that: Based on the total mass of the negative electrode plate, the mass proportion of water is 30ppm-110ppm.

10. The battery according to any one of claims 1 to 9, characterized in that The first lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide.

11. The battery according to any one of claims 1 to 10, characterized in that The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes LiMn x Fe 1-x-y M y PO4, wherein 0≤x≤1, 0≤y≤0.04, and M includes at least one of Ti, Mg, Ta, Sc, Cr, Y, Zr, Nb, Mo, La, Ta, W, Hf, V, Ni, Rh or Os.

12. The battery according to claim 11, characterized in that The BET specific surface area of ​​the positive electrode active material is 10 m 2 / g-15m 2 / g.

13. The battery according to claim 11 or 12, characterized in that: The positive electrode active material also includes a LiMn x Fe 1-x-y M y A coating material covering at least part of the surface of PO4, wherein the coating material comprises carbon.

14. The battery according to claim 13, characterized in that Based on the total mass of the positive electrode active material, the mass proportion of the coating material is 0.8%-3.5%.

15. The battery according to claim 13 or 14, characterized in that: Based on the total mass of the positive electrode active material, the mass proportion of the coating material is 1.3%-2.5%.

16. The battery according to any one of claims 1 to 15, characterized in that The negative electrode plate includes a negative electrode active material, and the negative electrode active material includes a silicon-based material.

17. The battery according to claim 16, characterized in that The volume average particle size Dv50 of the silicon-based material is less than or equal to 6 μm.

18. The battery according to claim 16 or 17, characterized in that: The volume average particle size Dv50 of the silicon-based material is 3 μm-6 μm.

19. The battery according to any one of claims 16 to 18, characterized in that Based on the total mass of the negative electrode active material, the mass proportion of the silicon-based material is 1%-5%.

20. The battery according to any one of claims 16 to 19, characterized in that The negative electrode active material further includes a second negative electrode active material, and the second negative electrode active material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material or lithium titanate.

21. The battery according to claim 20, characterized in that The volume average particle size Dv50 of the second negative electrode active material is 15 μm-20 μm.

22. The battery according to any one of claims 1 to 21, characterized in that The porosity of the negative electrode plate is 15%-25%.

23. The battery according to any one of claims 1 to 22, characterized in that The electrolyte further includes a second lithium salt, wherein the second lithium salt includes at least one of LiPF6, lithium difluorooxalatoborate, lithium dioxalatoborate or LiClO4.

24. The battery according to any one of claims 1 to 23, characterized in that The electrolyte further includes an additive, wherein the additive includes at least one of LiPO2F2 or LiSO3F.

25. The battery according to claim 24, characterized in that One or more of the following conditions are met: Based on the total mass of the electrolyte, the mass proportion of the LiPO2F2 is 0.1%-0.5%; Based on the total mass of the electrolyte, the mass proportion of the LiSO3F is 0.1%-0.5%.

26. The battery according to claim 24, characterized in that One or more of the following conditions are met: Based on the total mass of the electrolyte, the mass proportion of the LiPO2F2 is less than or equal to 0.2%; Based on the total mass of the electrolyte, the mass proportion of the LiSO3F is less than or equal to 0.1%.

27. The battery according to any one of claims 1 to 26, characterized in that Based on the total mass of the electrolyte, the mass proportion of the first lithium salt is 5%-10%.

28. A method for preparing a battery, characterized in that: include: Assembling the positive electrode sheet and the negative electrode sheet into a bare cell, injecting electrolyte, and obtaining a battery; Wherein, based on the total mass of the positive electrode plate, the mass proportion of water is 50ppm-300ppm, and based on the total mass of the negative electrode plate, the mass proportion of water is 30ppm-200ppm; the electrolyte includes a first lithium salt, and the first lithium salt includes: LiN(SO2R)2, Wherein, R includes at least one of F or a hydrocarbon group of 1 to 3 carbon atoms substituted by F, and based on the total mass of the electrolyte, the mass proportion of the first lithium salt is 3% to 10%.

29. The method according to claim 28, characterized in that Before injecting electrolyte, it also includes: The bare cell is dried.

30. The method according to claim 29, characterized in that One or more of the following conditions are met: The drying temperature is 100°C-120°C; The drying time is 10h-20h.

31. The method according to any one of claims 28 to 30, characterized in that After injecting the electrolyte, it also includes: The resulting battery.

32. An electrical device, characterized in that: A battery comprising the battery described in any one of claims 1 to 27 or a battery made by the method described in any one of claims 28 to 31.

Citation Information

Patent Citations

  • A method for bakomg large cylindrical lithium ion cell

    CN109119695A

  • Design method of transition layer between inorganic solid electrolyte and positive electrode

    CN110380133A

  • Electrode material composition, electrode plate and application thereof

    CN116154172A

  • Secondary battery and electric device

    CN117276463A

  • Ionic conductors

    US20230183090A1